The Sociological Perspectives in Case Study: Empowering Student Capability based Law in Action Method in Indonesia Legal Education - Rajib, Rayi Kharisma; Athar, Soultan; Bafaleo, Careno (The Indonesian Journal of International Clinical Legal Education, 2019)
Lack of application of law by the students in the life, is a problem thatmust be addressed immediately. The law is not just a "Law in Books",but must also "Law in Actions", Law in reality. And this is where thesociology of law plays an important role in making them. This paper willexamine how the sociological perspective to strengthen the capacity ofstudents based on the method of Law in Action in Education Law inIndonesia. As well as reviewing about the sociological perspective inlegal education, sociology of clinical legal education, a variety of casesthat occurred in the sociology of law and social law research. studentshave significant potential as a leading fighter in the change of theIndonesian nation. But not a few students who do not understand theirtrue responsibilities. And also do not know, understand and practice theTri Dharma Perguruan Tinggi which is a unity that cannot be separated,because the obligation of a student not only learn on campus for justscience, but he has obligations that must be borne in accordance withTri Dharma Perguruan Tinggi .